Mechanism of upconversion luminescence enhancement in Yb3+/Er3+ co-doped Y2O3 through Li+ incorporation. Issue 5 (21st January 2020) - Yang, Xiongfeng; Liu, Min; Liu, Jiandang; Xia, Yuanhua; Ji, Weiwei; Li, Zhiang; Chen, Jifang; Liu, Liu; Hao, Luyuan; Dong, Bingbing; Agathopoulos, Simeon; Xu, Xin
Abstract : Li + doping is a well-known, simple, yet efficient strategy to optimize the properties of upconverting materials. Abstract : Li + doping is a well-known, simple, yet efficient strategy to optimize the properties of upconverting materials. Nonetheless, the position of Li + in the lattice and the mechanism of upconversion enhancement are still controversial, especially in Yb 3+ /Er 3+ co-doped Y2 O3 . This paper presents a comprehensive investigation of the above issues ( i.e. the position occupied by Li + in the lattice and the mechanism of luminescence enhancement, in terms of decreased defects) by studying (Y0.78− X Yb0.20 Er0.02 Li X )2 O3 powders. Neutron powder diffraction was employed for the first time in the literature to show that Li + ions are accommodated in Y sites of YO6 octahedra, confirmed also by the content of oxygen defects, which was increased with the increase of Li + concentration. FT-IR showed that there was a small change in the amount and the type of the surface-absorbed groups with the increase in the Li + content, thus not supporting the prevailing conclusion that the quenching groups are decreased by doping Li + . Positron annihilation lifetime (PLAS) experiments showed that the total defect concentration and the large defect clusters, which are considered as quenching centers, are decreased with increasing Li + -content, resulting in the enhancement of the emission intensity in Yb 3+ /Er 3+ co-doped Y2 O3 .